The effect of financial education on college students’ knowledge and skills - Galarza Arellano, Francisco B. (2023)
There is a growing literature on the importance of adults’ financial education, especially in developed countries. The literature is less abundant when it comes to assessing the effect of financial education programs on the individuals’ financial knowledge and behavior, particularly in developing countries. This article evaluates the effect of Gestionando mis finanzas (GMF) on the financial knowledge and skills of college students in Peru. With a duration of one month, this virtual course of basic financial education was very effective in increasing the financial knowledge of the students. In addition to an increase by 0.96 standard deviations in the financial knowledge score, GMF had considerable effects on the self-perception of financial knowledge and mathematical skills, as well as on savings behavior. The effects on other aspects of financial behavior, such as price comparison before purchasing, price bargaining, and budgeting, were modest. I did not find any differential effect by sex, but I did observe a greater financial learning in students from higher socioeconomic levels.